2020
DOI: 10.1177/1420326x20919788
|View full text |Cite
|
Sign up to set email alerts
|

On-site measurement and simulation of indoor particulate matter distributed in a single room with stratified flow field

Abstract: This study combined on-site measurement and model simulation to characterize the spatial distribution of indoor particulate matter (PM) in a single room with stratified flow fields. The concentration of PM spatially distributed in a single room with natural ventilation was measured at different heights for different PM sizes. This study revealed that the PM concentration varied with height and time. Moreover, chamber test results showed that by burning Chinese worship incense, fine particles (PM0–4) accounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As a pathway on heat and pollutant transmission, airflow motion plays an important role. [17][18][19] Airflow drives heat and particle transport and can have an influence on the kitchen and indoor living environment. 20 There are some studies on airflow and particle transmission in terms of numerical simulation [21][22][23][24] and experimental measurements [25][26][27] in the kitchen and adjacent rooms.…”
Section: Introductionmentioning
confidence: 99%
“…As a pathway on heat and pollutant transmission, airflow motion plays an important role. [17][18][19] Airflow drives heat and particle transport and can have an influence on the kitchen and indoor living environment. 20 There are some studies on airflow and particle transmission in terms of numerical simulation [21][22][23][24] and experimental measurements [25][26][27] in the kitchen and adjacent rooms.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to high concentrations of PM 2.5 can cause various respiratory and cardiovascular diseases, and even increase the risk of early death. [4][5][6][7] Outdoor PM concentrations can significantly affect indoor air quality. 8 While previous studies have demonstrated an inverse relationship between PM and NAI, uncertainty regarding this relationship exists in urban residential areas where motor vehicles act as a common source of PM and NAI.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the outdoor environment, the indoor one is characterized by small space, high tightness and a large coupling effect. Lin et al 10 combined on-site measurement and model simulation to characterize the spatial distribution of indoor PM in a single room with stratified flow fields. Research shows that indoor air might contain many microorganisms and particulate matters that are easy to adsorb virus droplets and cause infections.…”
Section: Introductionmentioning
confidence: 99%